Interdependency in three Beckettian plays - Chiang, Michelle Hui Ling (2009)
Although noted by many literary scholars that a sense of interdependency between Samuel Beckett’s dramatic characters permeates the playwright’s work, the vast research done on Beckett’s drama seems to overlook the importance of this relationship between his characters. Referencing literary research done by, just to name a few, Martin Esslin, Edith Kern and John Fletcher, the aim of this essay is to extrapolate this relationship of interdependency in order to present to the reader, an alternative perspective on Beckett’s dramatic work. Examining the interdependent relationship of Beckett’s dramatic characters in Waiting for Godot, Endgame and Krapp’s Last Tape, interdependency can be figuratively translated into a framework of loops and their overlaps. The first chapter of this essay develops the basic concept of this framework. The idea of loops is derived from repetitive routines ascribed by the playwright to his dramatic characters as well as repeatedly unavailing dramatic dialogues between the characters. The second chapter posits that the interdependent relationships of the characters are derived from these interactions through routines and dialogues. In the framework of loops, this relationship of interdependency occurs when characters’ routine loops overlap. With this in mind, interdependency is observed to function as an important tool of distraction from the futility of their dramatic circumstances. The third and final chapter of this essay asserts further that interdependency functions not only as tool of distraction; it more importantly highlights an intrinsic “fellow-feeling” between humans that extends beyond a mere practical function of distraction.